2001
DOI: 10.1354/vp.38-1-116
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase-2 in Canine Renal Cell Carcinoma

Abstract: Cyclooxygenase-2 (COX-2) has been shown to be the primary enzyme responsible for prostaglandin production during inflammation but is absent in most tissues under normal physiological states. High levels of COX-2 expression have been observed in the macula densa and thick ascending limbs of fetal kidneys; this expression declines to minimal levels during renal maturation. We hypothesized that the neoplastic cells of renal cell carcinoma (RCC) may revert to high expression of COX-2, and we evaluated its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 10 publications
3
70
0
Order By: Relevance
“…In addition, inflammatory cells (presumptive macrophages and myofibroblasts) at ulcerated sites in five of the feline tumors displayed COX-2 immunoreactivity, which served as positive internal controls. The polyclonal antibody used in this study has detected COX-2 in canine tissues in previous studies 9,13 as well as in control canine tissues used in this study. These results suggest a basic species difference between feline and dog neoplasms in COX-2 expression.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, inflammatory cells (presumptive macrophages and myofibroblasts) at ulcerated sites in five of the feline tumors displayed COX-2 immunoreactivity, which served as positive internal controls. The polyclonal antibody used in this study has detected COX-2 in canine tissues in previous studies 9,13 as well as in control canine tissues used in this study. These results suggest a basic species difference between feline and dog neoplasms in COX-2 expression.…”
Section: Discussionmentioning
confidence: 88%
“…Expression of COX-2 has been reported in a few other types of cancers in dogs, including nasal tumors, renal cell carcinomas, ovarian carcinomas, oral melanomas, osteosarcomas, and meningiomas. 7,8,9,50,53,55,78,81,98 A high percentage (from 71-87%) of nasal epithelial tumors have been reported to overexpress COX-2, including various types of tumors (carcinomas, adenocarcinomas, squamous cell carcinomas, transitional, anaplastic). 8,50,55 A very small number (3) of renal cell carcinomas have been evaluated, with 2 cases being COX-2 positive.…”
mentioning
confidence: 99%
“…8,50,55 A very small number (3) of renal cell carcinomas have been evaluated, with 2 cases being COX-2 positive. 53 Borzacchiello et al 9 reported that 9 out of 11 ovarian carcinomas expressed COX-2 with an intensity ranging from faint to strong. Some oral melanomas have been reported to express COX-2, but treatment with cisplatin and piroxicam of dogs with oral melanomas had very limited success, with a remission in only 2 of 9 dogs with oral melanoma.…”
mentioning
confidence: 99%
“…COX-2 converts arachidonic acid first into prostaglandin G2, and afterwards by peroxidase activity into prostaglandin H 2, a precursor of the prostaglandins (Taketo 1998). COX-2 is suggested to play a physiological role in fetal nephrogenesis (Khan et al 2001). COX-2 increases in inflammation and neoplasia (Miyata et al 2003, Hara et al 2002, Nose et al 2002, et al Taketo 1998, and is undetectable in most normal tissues (Mungan et al 2006, Yoshimura et al 2004.…”
Section: Cox-2 Biomarker For Inflammation and Neoplasiamentioning
confidence: 99%